An Italian case series' description of thiamine responsive megaloblastic anemia syndrome: importance of early diagnosis and treatment - Francesca Di Candia; Valentina Di Iorio; Nadia Tinto; Riccardo Bonfanti; Claudio Iovino; Francesco Maria Rosanio; Ludovica Fedi; Fernanda Iafusco; Francesca Arrigoni; Rita Malesci; Francesca Simonelli; Andrea Rigamonti; et al. (BMC, 2023)
Abstract Background Individuals with thiamine-responsive megaloblastic anemia (TRMA) mainly manifest macrocytic anemia, sensorineural deafness, ocular complications, and nonautoimmune diabetes. Macrocytic anemia and diabetes may be responsive to high-dosage thiamine treatment, in contrast to sensorineural deafness. Little is known about the efficacy of thiamine treatment on ocular manifestations. Cases presentation Our objective is to report data from four Italian TRMA patients: in Cases 1, 2 and 3, the diagnosis of TRMA was made at 9, 14 and 27 months. In 3 out of 4 subjects, thiamine therapy allowed both normalization of hyperglycemia, with consequent insulin suspension, and macrocytic anemia. In all Cases, thiamine therapy did not resolve the clinical manifestation of deafness. In Cases 2 and 3, follow-up showed no blindness, unlike Case 4, in which treatment was started for megaloblastic anemia at age 7 but was increased to high doses only at age 25, when the genetic diagnosis of TRMA was performed. Conclusions Early institution of high-dose thiamine supplementation seems to prevent the development of retinal changes and optic atrophy in TRMA patients. The spectrum of clinical manifestations is broad, and it is important to describe known Cases to gain a better understanding of this rare disease.